Clinic, pathologic and molecular landscapes in ultra-young women with breast cancer in the State of São Paulo: a real-world study - Mattar, André; Yoshimura, Adriana Akemi; Fristachi, Carlos Elias; Pessoa, Eduardo Carvalho; Andrade, Felipe Eduardo Martins; Tosello, Giuliano; Vespoli, Heloísa Maria de Luca; Carneiro, Karina Belickas; Oliveira Jr., Idam de; Borges, João Bosco Ramos; Filassi, José Roberto; Gebrim, Luiz Henrique; et al. (Mastology, 2021)
Introduction: Breast cancer (BC) centers are increasingly attending “ultra-young” women (UYW) patients (≤ 30 years), who usually present aggressive tumors and face specific problems.Objectives: We aimed to examine a multicentric casuistic view, addressing clinicopathological and molecular characteristics of BC, as well as therapeutic measures and oncological outcomes. Methods: A retrospective multicentric observational study of UYW with infiltrating BC was carried out. The patients were treated between the period from January 1991 to December 2019. Clinical, epidemiological, morphological, molecular, therapeutic and outcomes data were collected from the charts. Results: A total of 293 patients were followed for a average period of 34.5 months. Nulliparity was referred by 204 women (75.5%), of whom 81 (37.1%) were overweight or obese. Positive family history in first-degree relatives was verified in 25 patients (10.1%). Only 30 patients underwent genetic tests, which revealed inherited pathogenic mutations in 12 of them (37.5%). Thirty-two (32) cases were classified as T1 at diagnosis (10.9%), while “De novo” stage IV was found in 29 patients (9.8%). Mastectomy was performed in 175 women (70.2%), quadrantectomy in 46 women (18.4%), and mammary adenectomies in 28 women (11.2%), of which 149 cases were reported after neoadjuvant chemotherapy (56.0%). A total of 111 patients had at least one positive lymph node (47.4%). The rate of patients with estrogen receptor-negative was 32.7% and the rate of patients with Human Epidermal Growth Factor Receptor 2-positive (HER2-positive) was 25%. The frequency of Luminal A neoplasias was 16.6%, Luminal B/HER2- was 35.9%, Luminal B/HER2+ was 15.1%, HER2 overexpressed was 9.3%, and Basal was 22.9%. Taking into account the outcomes, 173 patients were alive without disease (65.7%); 23 patients were alive with any form of recurrence (8.7%); and 67 patients (25.4%) evolved to BC deaths. Conclusions: It was concluded that UYW with BC are commonly diagnosed at advanced stages, present adverse morphological and molecular parameters, and have unfavorable prognosis.